2023
DOI: 10.3390/biom13010128
|View full text |Cite
|
Sign up to set email alerts
|

Selenium-Substituted Monomethine Cyanine Dyes as Selective G-Quadruplex Spectroscopic Probes with Theranostic Potential

Abstract: The binding interactions of six ligands, neutral and monocationic asymmetric monomethine cyanine dyes comprising benzoselenazolyl moiety with duplex DNA and RNA and G-quadruplex structures were evaluated using fluorescence, UV/Vis (thermal melting) and circular dichroism (CD) spectroscopy. The main objective was to assess the impact of different substituents (methyl vs. sulfopropyl vs. thiopropyl/thioethyl) on the nitrogen atom of the benzothiazolyl chromophore on various nucleic acid structures. The monomethi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…This method has been successfully applied to the synthesis of both symmetrical and unsymmetrical MCDs (Figure 3): This method was used in a recent work [8] for the synthesis of symmetrical MCDs with various terminal heterocyclic groups and substituents at nitrogen atoms. It is also widely used for the synthesis of unsymmetrical MCDs with different heterocyclic residues [9][10][11][12]. The thioalkyl method was applied in the synthesis of a number of MCDs derived from SYBR green II [13].…”
Section: Synthesis Of Mcdsmentioning
confidence: 99%
See 2 more Smart Citations
“…This method has been successfully applied to the synthesis of both symmetrical and unsymmetrical MCDs (Figure 3): This method was used in a recent work [8] for the synthesis of symmetrical MCDs with various terminal heterocyclic groups and substituents at nitrogen atoms. It is also widely used for the synthesis of unsymmetrical MCDs with different heterocyclic residues [9][10][11][12]. The thioalkyl method was applied in the synthesis of a number of MCDs derived from SYBR green II [13].…”
Section: Synthesis Of Mcdsmentioning
confidence: 99%
“…The interaction of new unsymmetrical MCD 20-26 (Figure 14), containing a benzoselenazole fragment, with dsDNA/RNA was studied in [11,12]. It has been shown that the dyes interact with dsDNA with significant fluorescent growth; the dyes containing a methyl group at the nitrogen atom in the benzothiazole core (dyes 20 and 21) were found to be more suitable as fluorescent markers (up to a 63-fold increase in the fluorescence intensity in the presence of dsDNA).…”
Section: Monomeric MCDmentioning
confidence: 99%
See 1 more Smart Citation
“…A wide range of biological and biomedical systems currently being studied with the use of spectral fluorescent probes stimulates a permanent emergence of research aimed at developing new efficient and selective dye probes for the detection and staining of biomolecules in such systems (see, e.g., [ 16 , 17 , 18 ]). There are a large number of works by different research groups devoted to the synthesis and spectral fluorescent study of various MCDs (symmetrical and unsymmetrical) in order to develop probes for nucleic acids [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ]. There are also some works directed to the study of primary photophysical and photochemical processes in MCD molecules, both free and noncovalently bound to nucleic acids [ 35 , 36 , 37 , 38 , 39 , 40 ] (see also the review [ 41 ]).…”
Section: Introductionmentioning
confidence: 99%
“…2023, 24, x FOR PEER REVIEW 2 of 27 molecules in such systems (see, e.g., [16][17][18]). There are a large number of works by different research groups devoted to the synthesis and spectral fluorescent study of various MCDs (symmetrical and unsymmetrical) in order to develop probes for nucleic acids [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34]. There are also some works directed to the study of primary photophysical and photochemical processes in MCD molecules, both free and noncovalently bound to nucleic acids [35][36][37][38][39][40] (see also the review [41]).…”
Section: Introductionmentioning
confidence: 99%